Development and Validation of the Relational Needs Satisfaction Scale - Žvelc, Gregor; Jovanoska, Karolina; Žvelc, Maša (Frontiers in Psychology, 2020)
The aim of the research was the development of a new scale for measuring the satisfaction of relational needs. In the first study, we developed 269 items based on Erskine’s description of eight relational needs. Five experts evaluated the items, and then they were pilot-tested on a sample of 221 participants. Using principal component analysis, we found five components related to five relational needs: authenticity, support and protection, having an impact, shared experience, and initiative from the other. In the second study, the Relational Needs Satisfaction Scale was tested on a sample of 255 participants and further refined with the help of factor analysis. The final version of the scale consists of 20 items and measures overall relational needs satisfaction and the five dimensions of relational needs. The reliability of the overall score was excellent, while subscales had acceptable to good reliability. The relational needs satisfaction positively and significantly correlates with the secure attachment style, self-compassion, higher satisfaction with life, and better well-being. In the third study, we confirmed both the five-factor model and the hierarchical model on the sample of 354 participants. We proposed that the hierarchical model is more congruent with the theoretical model, as all five dimensions of relational needs are aspects of one general dimension of relational needs satisfaction. The scale can be used in both psychotherapy and counseling and research related to different fields of psychology.